Study of temperature calculation in hydrogen storage tank filled with metal hydride - Masahiro MATSUSHITA; Mitsumasa IINO; Ikko TAJIMA; Masatake ABE; Hideki TOKUYAMA (Nihon Kikai Gakkai ronbunshu, 2020)
The temperature calculation of a practical hydrogen storage tank filled with a metal hydride under development was carried out. The metal hydride was a nano-stractured FeTi (n-FeTi) by mechanical alloying, which has low particle decay and low price. The governing equations used in the calculation were the unsteady two-dimensional heat conduction equations. Expansion and contraction of metal hydride due to hydrogen storage and release were considered as changes in porosity and changes in thermal properties. The change in porosity was treated as the change in energy generated per unit volume. For changes in thermal properties, the empirical formulas based on our experiments were used for the changes in effective thermal conductivity and effective thermal diffusivity due to hydrogenation. A hydrogen storage tank was actually manufactured, and the experimental and calculated results were compared. From the results, it is considered that the use of empirical formulas is important for improving the reliability of calculation results because the change in thermal properties of the packed bed of hydrogen storage alloy due to hydrogenation affects the temperature distribution. In addition, the effect of the presence or absence of heat transfer enhancement fins was evaluated by the calculation. As a result, this calculation can be used to design the heat transfer enhancement fins for hydrogen storage tanks.